Republic of Armenia : Third Review Under the Extended Arrangement, and Request for Waiver and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Republic of Armenia. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Armenia's Third Review Under the Extended Arrangement, and Request for Waiver and Modification of Performance Criteria (PC). Growth in Armenia is expected to remain subdued as recession in Russia continues and as the base effects of the 2015 one-off factors dissipate. The program performance has been broadly satisfactory. All end-December 2015 PCs, except for the fiscal deficit PC, and all the continuous PCs were met. The fiscal deficit PC was missed by 0.3 percent of GDP. The IMF staff supports completion of the review and the authorities' request for a purchase in an amount equivalent to SDR 15.65 million.